Literasi Digital dan Teknologi Komunikasi Interpersonal (Studi Kasus Penipuan melalui “Kencan Online” di Media Sosial) - DESSY KUSHARDIYANTI; Novy Khusnul Khotimah; Ana Humardhiana; Rani Ika Wijayanti; Misbah Binasdevi (Holistik, 2022)
The development of Information Communication Technology (ICT) became the trigger of changes in the process of interpersonal communication. Social Media became one of the platforms that many trigger the development of interpersonal communication process, especially in forming an intimate relationship. "Online Dating" many done by some users of social media to find a life partner or just as a mere entertainment. However, there are many cases of fraud to the threat posed by "online dating" itself. Some perpetrators even use open information from victims to achieve more intimate relationships. Understanding related digital literacy and self disclosure in this case need more deeper and how the application of Social Media Literacy (SML). Understanding of the stages of the process of the formation of interpersonal communication relationships to the intimate stage needs to be done to avoid negative impacts arising from interpersonal communication within the scope of social media.